Chinese Undergraduates’ Performance in HOTS and LOTS EFL Reading Comprehension for Different Reading Materials According to Gender - Lingfeng, Li; Nair, Subadrah Madhawa (Contemporary Research in Education and English Language Teaching, 2021)
Many studies indicate that Chinese undergraduates face problems in their HOTS comprehension. The objective of this study is to investigate Chinese EFL undergraduates’ HOST and LOTS reading comprehension according to gender. A descriptive research design was employed in this quantitative study. The researchers used an English reading comprehension test involving 5 different materials (education, economy, entertainment, technology and natural disaster) as the research instrument. Each material consists of 3 LOTS questions and 2 HOTS questions. All the comprehension questions were multiple choice in nature. The sample of the study consists of 411 second year undergraduate students (261 females and 150 males) from a university in Hunan Province, China. SPSS Program for Windows version 25 was used to analyze the data (Independent samples t-test). The findings of this current study indicated that the female students performed significantly better than their male counterparts for both LOTS and HOTS comprehension questions. The female students also outperformed their male students in their overall score for comprehension. As such, these results clearly revealed that female undergraduates performed significantly better than the males in their EFL reading comprehension skills. However, this research only involves participants from one university; as a result, future research should include a larger sample from different provinces in China to get a better insight of students’ performance in EFL comprehension.